Genetics, prevalence, screening and confirmation of primary aldosteronism: a position statement and consensus of the Working Group on Endocrine Hypertension of The European Society of Hypertension*. Issue 10 (October 2020) - Mulatero, Paolo; Monticone, Silvia; Deinum, Jaap; Amar, Laurence; Prejbisz, Aleksander; Zennaro, Maria-Christina; Beuschlein, Felix; Rossi, Gian Paolo; Nishikawa, Tetsuo; Morganti, Alberto; Seccia, Teresa Maria; Lin, Yen-Hung; et al.
Abstract : N/A: Autonomous aldosterone overproduction represents the underlying condition of 5–10% of patients with arterial hypertension and carries a significant burden of mortality and morbidity. The diagnostic algorithm for primary aldosteronism is sequentially based on hormonal tests (screening and confirmation tests), followed by lateralization studies (adrenal CT scanning and adrenal venous sampling) to distinguish between unilateral and bilateral disease. Despite the recommendations of the Endocrine Society guideline, primary aldosteronism is largely underdiagnosed and undertreated with high between-centre heterogeneity. Experts from the European Society of Hypertension have critically reviewed the available literature and prepared a consensus document constituting two articles to summarize current knowledge on the epidemiology, diagnosis, treatment, and complications of primary aldosteronism. Abstract : Supplemental Digital Content is available in the text